(untitled) (Revista Direito em Debate, 2021)
This paper analyses the case of slave labor in the State of Amazonas, in the municipality of Barcelos in 2014. The action against slave labor in Brazil has come to be expressed through the amendment of the Brazilian Penal Code and the Federal Constitution. Today, contemporary slavery is a violation of human and worker dignity, and despite existing laws and interventions, slavery persists in new forms. The rescue of 13 workers in conditions analogous to that of a slave in Barcelos demonstrates the importance of inspection and participation of public agencies. However, the action against slave labor requires the regulation of extractive activity and the elimination of aviation in conjunction with precise laws and effective inspection.